Effects of starch pre-gelatinization on growth performance and feed utilization of Chinese soft-shelled turtle (Pelodiscus sinensis) - JIA Yanju; WANG Haiyan; LIAO Xing; CHEN Qiuxin; WEI Jiamin; ZHENG Xiaotong; SONG Ruixue; LI Jian (浙江大学学报. 农业与生命科学版, 2016)
Carbohydrate is considered the least expensive form of dietary energy for animals. The ability of farmed fish to use dietary carbohydrates as an energy source is generally lower than that of terrestrial livestock. The relative efficiency of dietary carbohydrate utilization by fish has been associated with dietary carbohydrate level, molecular complexity and the technological treatments applied. Starch is the main source of dietary carbohydrate in aquafeed, and pre-gelatinization is a widely used method to improve the starch utilization. Many researches showed that gelatinized starch is more significant in carnivores to improve feed digestion and utilization. However, some experiments reported that total gelatinization of diet starch would not has positive effect on the growth of some fish. Chinese soft-shelled turtle (Pelodiscus sinensis) is carnivore, which was reported had low ability to use dietary carbohydrates. Pre-gelatinized starch is used universally in Chinese turtle diet now, but the ability to use raw starch is still unknown. This experiment was conducted to evaluate if starch pre-gelatinization could increase the growth and feed utilization of P. sinensis.Four test diets were designed with adding the same level of cassava starch (20%), but different replacement ratio of pre-gelatinized starch by raw starch (0%, 33%, 67% and 100%). Nutritional compositions of four test diets were similar, with about 46% protein, 9% fat and 16 kJ/g energy. The feeding experiment lasted for 7 weeks. Chinese turtles with initial average body mass of 6.5 g were fed twice a day at (30±1)℃. The feeding rate, specific growth rate, feed conversion ratio, protein efficiency ratio, viscera-somatic index, hepatosomatic index, nutrient digestibility, and body composition of turtle were analyzed.Differences in specific growth rate, viscera-somatic index, hepatosomatic index, digestibility of dry mass, protein and fat of Chinese turtle fed different diets were all insignificant (P<0.05). However, starch pre-gelatinization affected feeding rate, feed conversion ratio and protein efficiency ratio. Feeding rate increased with the replacement ratio of pre-gelatinized starch by raw starch, and protein efficiency ratio decreased linearly. Feeding rate of turtle fed diet 1 was significantly higher than those fed diet 3 and 4. Protein efficiency ratio of turtle fed diet 1 and 2 were both significantly lower than those fed diet 3 and 4, differences in protein efficiency ratio of the groups between diet 1 and 2 and between diet 3 and 4 were both insignificant. Feed conversion ratio increased significantly with the total replacement of pre-gelatinized starch by raw starch. Feed conversion ratio of turtle fed diet 1 and 2 were both significantly higher than those fed diet 3 and 4. Contents of body water, protein, fat, ash and energy of turtle fed different diets were all different insignificantly.Those results indicate that Chinese turtle has a good ability to use raw starch, and the growth performance of P. sinensis is not affected by starch pre-gelatinization, but feed utilization can be enhanced. Since the price of pre-gelatinized starch is higher than that of the raw starch, the raw cassava starch can be used and totally replace the pre-gelatinized cassava starch in the Chinese turtle diet.